(untitled) (Pedagogical Cluster-Journal of Pedagogical Developments, 2023)
Pedagogical observations show that the use of the design method in the physical education classes of schoolchildren, in sports activities on cheerful starts, turns the physical education class from a class of movement activity into an educational class, and puts it on a par with other basic subjects.